The Effect Of Job Satisfaction And Work Life Balance On Employee Performance Through Work Loyalty At PT. Ottomitra Multiartha (WOM) Sidoarjo Branch - Prastiyono, Suryo; Sutoyo; Zainuddin, Ahmad; Suminar, Lintang; Soleha, Siti Nur (PT Maju Malaqbi Makkarana, 2025)
This study aims to prove and analyze the influence of Job Satisfaction and Work Life Balance on Employee Performance at PT. Wahana Ottomitra Multiartha (WOM) Sidoarjo Branch, both directly and through Work Loyalty as an intervening variable. The research population was all employees of the sales marketing division, as many as 112 people, who were used as a sample using the saturated sample technique. The analysis method used is Partial Least Squares (PLS) to test the seven hypotheses proposed. The results of the study show that Job Satisfaction and Work Life Balance have a positive and significant effect on Employee Performance. In addition, Job Satisfaction and Work Life Balance also have a positive effect on Job Loyalty. Work Loyalty itself has been proven to have a positive and significant influence on Employee Performance. Job Loyalty also plays a role as a mediating variable that strengthens the influence of Job Satisfaction and Work Life Balance on Employee Performance.